2003
DOI: 10.2466/pms.2003.96.3c.1062
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Factors in Sex Differences on Mental Rotation

Abstract: Past research has shown that men score significantly higher than women on mental rotation tests. The present study examined the effects of a prior exposure to a mental rotation task, i.e., adapted Cube Comparison test, and to three-dimensional objects, i.e., Legos, on the performance on the Mental Rotation Test. 113 men and women were randomly divided into three conditions: control, exposure, or detailed instructions. On average, men outperformed women. Further analyses showed that sex differences were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Boys tend to spend significantly more time than girls in spatial activities (Cherney & London, 2006) and may thus benefit from these experiences more than girls. Several studies have examined the importance of spatial experiences on visuospatial skills (e.g., Voyer, Nolan, & Voyer, 2000;Cherney, Jagarlamudi, Lawrence, & Shimabuku, 2003). For example, Terlecki, Newcombe, and Little (2008) as well as Cherney (2008) showed that training and practice with videogames can eliminate visuospatial sex differences, suggesting that spatial skills can be learned.…”
Section: Discussionmentioning
confidence: 99%
“…Boys tend to spend significantly more time than girls in spatial activities (Cherney & London, 2006) and may thus benefit from these experiences more than girls. Several studies have examined the importance of spatial experiences on visuospatial skills (e.g., Voyer, Nolan, & Voyer, 2000;Cherney, Jagarlamudi, Lawrence, & Shimabuku, 2003). For example, Terlecki, Newcombe, and Little (2008) as well as Cherney (2008) showed that training and practice with videogames can eliminate visuospatial sex differences, suggesting that spatial skills can be learned.…”
Section: Discussionmentioning
confidence: 99%
“…MR performance is influenced by both circulating sex hormones (Aleman, Bronk, Kessels, Koppeschaar, & van Honk, 2004;Hampson, 2018;Hausmann, Slabbekoorn, Van Goozen, Cohen-Kettenis, & Güntürkün, 2000) and exposure to sex hormones early in development (Alexander & Son, 2007;Falter, Arroyo, & Davis, 2006;Grimshaw, Sitarenios, & Finegan, 1995). In addition, numerous studies have demonstrated that MR performance can be improved with training (Baenninger & Newcombe, 1989;Cherney, Jagarlamudi, Lawrence, & Shimabuku, 2003;Fernández-Méndez, Contreras, & Elosúa, 2018;Sanz de Acedo Lizarraga & García Ganuza, 2003). These studies provide evidence for both biological and environmental influences on MR, and they raise vital questions about the influences of hormones and experiences on development of MR.…”
Section: Mental Rotation Of 3d Objectsmentioning
confidence: 99%
“…In a third study, 5 ½ hours of video game play erased the sex difference (De Lisi and Wolford 2002). In a fourth, just two minutes of practice before the test erased the different performance levels of men and women (Cherney et al 2003).…”
Section: Brain ⁄ Environment Interactionsmentioning
confidence: 99%